2022
DOI: 10.1097/ta.0000000000003745
|View full text |Cite
|
Sign up to set email alerts
|

The Beirut ammonium nitrate blast: A multicenter study to assess injury characteristics and outcomes

Abstract: BACKGROUND:Blasts incidents impose catastrophic aftermaths on populations regarding casualties, sustained injuries, and devastated infrastructure. Lebanon witnessed one of the largest nonnuclear chemical explosions in modern history-the August 2020 Beirut Port blast. This study assesses the mechanisms and characteristics of blast morbidity and mortality and examines severe injury predictors through the Injury Severity Score. METHODS:A retrospective, multicenter cross-sectional study was conducted. Data of trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
(87 reference statements)
3
3
0
1
Order By: Relevance
“…Post-injury vital signs indicated an increased HR, a decreased MAP, and an increased SI, aligning with the changes observed in central hemodynamic parameters (CI and SVI), volumetric parameters (GEDI and ITBI), and vascular peripheral resistance (SVRI). These findings are consistent with the lung ultrasonography scores and anatomical observations, corroborating previous clinical retrospective studies and laboratory research on blast injuries ( Zhang et al, 2015 ; Yuanbo et al, 2016 ; Tong et al, 2018 ; Smith and Garner, 2019 ; April et al, 2021 ; Carius et al, 2022 ; Al-Hajj et al, 2023 ). Previous studies have demonstrated that prompt and effective arterial blood gas analysis following BLI is crucial for diagnosing conditions and developing treatment plans ( Manera et al, 2020 ; Xue et al, 2020 ; Chong et al, 2021 ; Shi et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Post-injury vital signs indicated an increased HR, a decreased MAP, and an increased SI, aligning with the changes observed in central hemodynamic parameters (CI and SVI), volumetric parameters (GEDI and ITBI), and vascular peripheral resistance (SVRI). These findings are consistent with the lung ultrasonography scores and anatomical observations, corroborating previous clinical retrospective studies and laboratory research on blast injuries ( Zhang et al, 2015 ; Yuanbo et al, 2016 ; Tong et al, 2018 ; Smith and Garner, 2019 ; April et al, 2021 ; Carius et al, 2022 ; Al-Hajj et al, 2023 ). Previous studies have demonstrated that prompt and effective arterial blood gas analysis following BLI is crucial for diagnosing conditions and developing treatment plans ( Manera et al, 2020 ; Xue et al, 2020 ; Chong et al, 2021 ; Shi et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…Currently, both nationally and internationally, there is a paucity of research on the changes in respiratory mechanics following severe BLI. Most animal-based studies have focused on the mechanisms of injury, post-injury pathophysiological alterations, and their underlying molecular mechanisms ( Scott et al, 2017 ; Nguyen et al, 2019 ; Smith and Garner, 2019 ; Hazell et al, 2022 ; Shakargy et al, 2022 ; Al-Hajj et al, 2023 ). There has been insufficient exploration into the maintenance programs for post-injury respiratory function, especially those concerning variations in respiratory mechanics parameters monitored by Pes in animals afflicted with severe BLI; such studies are notably absent in the existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…The high incidence of laceration injuries aligns with previous studies on the Beirut injuries [7], [10], which can be attributed to people being close to their windows to watch or film the initial fire before the blast [17]. Very few participants reported having 'internal injuries' (N=11) with a total of four reporting tympanic membrane (eardrum) rupture.…”
Section: Blast Injury Patterns and Injury Severitysupporting
confidence: 80%
“…Previous investigations into the injury patterns resulting from the Beirut blast have consistently noted a substantial prevalence of secondary blast injuries, primarily attributed to extensive failure of glazing [7]- [10]. However, these earlier studies lack accurate documentation of victims' locations at the time of the explosion.…”
Section: Introductionmentioning
confidence: 99%
“…The 2020 Beirut port explosion, which was the largest non-nuclear explosion in recent history, was caused by the detonation of 2750 tons of inappropriately stored ammonium nitrate fertilizer; this explosion, occurring in an urban environment, resulted in over 6000 civilian injuries and 200 fatalities [ 10 ]. A multicentre study of the injury characteristics of patients presenting at emergency departments after the Beirut explosion found that 6.2% had concussion originating from primary blast exposure [ 11 ]. The current (2022) conflict in Ukraine has seen cities and civilian infrastructure targeted by artillery and guided weapons [ 12 ].…”
Section: Introductionmentioning
confidence: 99%